13 Musculoskeletal injuries sustained by female national league hockey players. (13th October 2015) - Bolton, S; Nahas, S; Gibb, P
Abstract : The aim was to determine the prevalence and spectrum of injuries that female national league hockey players sustain. A retrospective questionnaire was conducted during the Investec English National Hockey league indoor competition. Players under the age of 16 were excluded from the data collection. Demographics, protective equipment worn, warm up and cool down style as well as injury profile were obtained. The sample consisted of 61 players who returned completed questionnaires. The average age of the players was 25 y. 64% of players reported  1–2 injuries over the past year (n = 39). 15% of players reported that they were currently playing with an injury (n = 9). 64% of injuries were in the lower limb, with the knee being most commonly injured. A high proportion of hockey players sustain musculoskeletal injuries and still play in spite of being injured. A large proportion of players do not wear protective equipment, eg gum shields, as this is not compulsory. Future studies should look to work with England Hockey to reduce and prevent injuries among national league and hockey players of all levels.